Provinciale Prijs voor Kunstambachten en Industriële Vormgeving 2000 : Keramiek. - Minten, Chris; Leplae, Wendy (Brugge : Provincie West-Vlaanderen, 2001)
Blomme, Greet ; Boeraeve, Gerd ; Caluwier, Carlos ; Debruyne, Iris ; Delrue, Rik ; Dessauvage, Tjok ; Dewaele, Koenraad ; Deweerdt, Tine ; Dhuyvettere, Norbert ; Fischer, Dorine ; Haelewyn, Monique ; Huyghe, Stefaan ; Kolmeyer, Nicolien, Lee, Yoon-Kyung ; Lefevre, Natasja ; Suykens, Hilde ; Vancoppenolle, Marleen ; Vandekerckhove, Stijn ; Verduyn, Claude ; Vermoere, Gerda
boek
Keywords: Minten Chris